THE ROLE OF THE GOVERNMENT AND CUSTOMARY INSTITUTIONS IN RESOLUTION OF THE CONFLICT BETWEEN PT. ADINDO HUTANI LESTARI AND THE COMMUNITY OF TUJUNG VILLAGE, REGENCY - Jahari; Oscar Jayanagara; Vivi Indra Amelia Nasution (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The Role of the Nunukan Regency Government and the Dayak Agabag Traditional Institution in resolving the tenurial conflict between the Tujung Village community and PT. Adindo Hutani Lestari in North Kalimantan. The study used a qualitative approach with a case study design through in-depth interviews, observations, and document reviews to obtain contextual and in-depth understanding. The results of the study indicate that the Traditional Institution acts as a negotiator, communication link, and facilitator based on cultural values ​​in articulating the community's collective aspirations, while the Regional Government acts as a facilitator, mediator, and conflict resolution actor through legislative policies and mediation mechanisms that produce mutual agreements. The synergy between the Regional Government and the Traditional Institution shows that conflict resolution is not only related to legal aspects, but also includes social, cultural, and community food security dimensions. This study has managerial implications for strengthening the role of traditional institutions and the government in land conflict governance and opens up opportunities for developing new conceptual models in the study of local wisdom-based conflict management.